Prehistoric and pre-Islamic burial archaeology in Qatar: new results and perspectives (poster) - Zamora, Áurea Izquierdo; Cuttler, Richard T.H.; al-Naimi, Faisal Abdulla (Proceedings of the Seminar for Arabian Studies, 2015)
While research since the 1950s has greatly contributed to the understanding of pre-Islamic burial practices in Qatar, there remain several periods for which the absence of comprehensive absolute chronologies remains an obstacle. More recently the presence of c Ubaid pottery within several burials and the discovery of two new burials types has led us to reassess our understanding of the archaeology of death and burial in Qatar. New research conducted by the QNHER Project during the 2013-2014 season has revealed the first example of a fourthmillennium burial in Qatar. These recent results provide the foundation for a robust framework of research within the wider area. This paper will review the background research for burial archaeology in Qatar, with special attention to Wādī Ḍabayʿān; and the detailed results of the excavation of burial cairns in Wādī al-Jaltah (north-eastern Qatar) and the excavation of tombs in al-Ghāfāt (central Qatar). Excavations at both sites revealed complex and extensive chronologies which have provided a range of important proximal data. Given the absence of settlement sites, the systematic excavation and recording of burial sites is fundamental to our comprehension of pre-Islamic social groups. Prehistoric archaeology represents a key period in the development, migration, and establishment of early societies within the Arabian Peninsula. These sites not only contribute to national historical narratives but they are also essential in terms of understanding the development and dispersal of early human societies within an international context.